Dehydration of subducting slow-spread oceanic lithosphere in the Lesser Antilles - Michele Paulatto (Nature Portfolio, 2017)
During subduction water is transported into the mantle, but constraining its release remains challenging. Here, using seismic tomography of the Lesser Antilles arc, the authors track the multistage dehydration of the slab and its lateral variations associated with heterogeneous slab composition.